2015
DOI: 10.1016/j.nedt.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up nurse education: An evaluation of a national PhD capacity development programme in South Africa, in the context of the global shortage of nursing graduates

Abstract: . Abstract BackgroundThe global shortage of nursing professionals educated at baccalaureate level and beyond has been highlighted. Within America, services are preparing to treat an additional 32 million individuals under the new Health Reform Bill. Within South Africa the existing nursing education outputs do not meet service demands. Many countries are addressing these shortages by developing advanced nursing roles which require research degrees. Objective:To evaluate a national nursing PhD development progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 14 publications
0
18
0
1
Order By: Relevance
“…The implementation did provide an ideal microclimate for learning and development. Of those who did participate, in support of previous literature, this study found allocating time for research was still an ongoing challenge [5, 8, 9, 11, 12, 18, 19]. It is still difficult for research to be seen as a priority given clinical commitments in spite of supports at senior level.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…The implementation did provide an ideal microclimate for learning and development. Of those who did participate, in support of previous literature, this study found allocating time for research was still an ongoing challenge [5, 8, 9, 11, 12, 18, 19]. It is still difficult for research to be seen as a priority given clinical commitments in spite of supports at senior level.…”
Section: Discussionmentioning
confidence: 52%
“…While there is an identified inconsistency in the meaning of the term research capacity building, within this paper it refers to involvement at all levels of the research process from question design to dissemination [5, 8]. Research capacity building has been identified as a priority in nursing research and development [5, 9]. However, within nursing to date the emphasis in research capacity building has been mainly in nurse academics [5, 9, 10], rather than in nurses with a clinical role [7, 9, 11, 12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increase in the number of nurses undertaking a PhD globally (Evans and Stevenson 2011) and strategies to develop programmes, for example, in countries such as South Africa (Comiskey 2015), together with the growth of the Professional Doctorate (Smith 2013) is helping nursing to be taken seriously as a research based profession in two key ways. Firstly, in developing an evidence base that can help the profession deliver on the drive to increase quality, innovation, productivity and preventative measures (Department of Health 2010).…”
Section: Introductionmentioning
confidence: 99%